Spanish-to-German Translations of Olive Oil Export Company Websites: a Focus on Geographical Indication and Olive Oil Category terminology - Limbach, Christiane (HERMES - Journal of Language and Communication in Business, 2025)
According to a report by the Spanish Ministry of Agriculture, Fishing and Nutrition (2022), olive oil accounted for a total turnover of 148.39 million euros in 2021, making olive oil Spain’s fifth agricultural product in terms of sales volume. Approximately one third of all production is exported, Germany leading European exports with 258 tons (t) of olive oil. Product descriptions must be translated for foreign markets, and in this case, particular attention must be paid to the terms used to describe olive oil quality, notably the geographical indications and olive oil categories. Terminological research (Ibañez Rodríguez, 2003) is thus a key dimension of translation here: the selected words must be recognisable by potential foreign customers, and they must be in line with the terminology established by the European Commission. In this study, we worked on a corpus of websites of Andalusian small and medium-sized enterprises (SMEs) in both German and Spanish. These SMEs all actively produced and sold olive oil and had an EU geographical indication register. In order to analyse how geographical indications and olive oil categories were translated from Spanish into German and to determine whether EU terminology was applied, we used the Sketch Engine programme. We found a wide range of translations which were potentially creating misunderstandings and raising doubts in the minds of German consumers.